Managing PVR in the Era of Small Gauge Surgery - Manish Nagpal; Rakesh Juneja; Sham Talati (Journal of Ophthalmology)
Proliferative vitreoretinopathy (PVR) is the leading cause of failed rhegmatogenous retinal detachment (RRD) surgery. Based upon the presence of clinical features and due to associated underlying risk factors, it is classified into various grades based upon its severity and extent of involvement. Despite excellent skills, flawless techniques, and high-end technology applied in the management of RRD, PVR still occurs in 5–10% of cases. Due to the advancements in wide angle viewing systems, advance vitrectomy machines and fluidics, early identification, use of long-term heavy silicon oil tamponades, high-speed cutters, small-gauge vitrectomies, use of perfluorocarbon liquid (PFCL), and small-gauge forceps and scissors, the success rate in the management of PVR has increased leading to improved anatomical outcomes. However, functional outcomes do not correlate well with improved anatomical outcomes. Various complications occur after RRD repair that are responsible for re-retinal detachment and recurrence of PVR. This article highlights causes, risk factors, classification, grading, diagnosis, and approach to management of PVR and post-PVR surgery complications.